Genomic Insights Into the Lifestyles of Thaumarchaeota Inside Sponges - Haber, Markus; Burgsdorf, Ilia; Handley, Kim M.; Rubin-Blum, Maxim; Steindler, Laura (Frontiers in Microbiology, 2021)
Sponges are among the oldest metazoans and their success is partly due to their abundant and diverse microbial symbionts. They are one of the few animals that have Thaumarchaeota symbionts. Here we compare genomes of 11 Thaumarchaeota sponge symbionts, including three new genomes, to free-living ones. Like their free-living counterparts, sponge-associated Thaumarchaeota can oxidize ammonia, fix carbon, and produce several vitamins. Adaptions to life inside the sponge host include enrichment in transposases, toxin-antitoxin systems and restriction modifications systems, enrichments previously reported also from bacterial sponge symbionts. Most thaumarchaeal sponge symbionts lost the ability to synthesize rhamnose, which likely alters their cell surface and allows them to evade digestion by the host. All but one archaeal sponge symbiont encoded a high-affinity, branched-chain amino acid transporter system that was absent from the analyzed free-living thaumarchaeota suggesting a mixotrophic lifestyle for the sponge symbionts. Most of the other unique features found in sponge-associated Thaumarchaeota, were limited to only a few specific symbionts. These features included the presence of exopolyphosphatases and a glycine cleavage system found in the novel genomes. Thaumarchaeota have thus likely highly specific interactions with their sponge host, which is supported by the limited number of host sponge species to which each of these symbionts is restricted.